Does fit perception influence career exploration in a relational context? the mediating role of career adaptability - Kou, Qi; Mohd Rasdi, Roziah; Muhamad Nasharudin, Nurfazreen Aina; Md Rami, Ahmad Aizuddin; Cao, Peng; Umar Baki, Nordahlia (Emerald Publishing, 2023)
Purpose: this study aims to examine the relationship between contextual factors and career exploration. Career adaptability mediates the relationship between social support, sense of belonging and career exploration. Design/methodology/approach: this quantitative study involved 291 undergraduates recruited from two universities in China. Data were analyzed using structural equation modeling. Findings: the results indicated that social support and sense of belonging were positively related to career adaptability. Career adaptability was found to be a mediator between relational predictors and career exploration. Contrary to our hypothesis, the direct path from sense of belonging to career exploration was insignificant. Originality/value: this study highlights the importance of career adaptability in connecting contextual indicators and career exploration in the Chinese context.